Damage characteristics and catastrophic failure mechanism of coal rock induced by gas adsorption under compression - Xiaochun Xiao; Lei Wang; Jun Xu; Xiangfeng Lv; Pengfei Guo; Yishan Pan (Journal of Rock Mechanics and Geotechnical Engineering, 2020)
To reveal the damage characteristics and catastrophic failure mechanism of coal rock caused by gas adsorption, physical tests and theoretical methods are employed. The results show that adsorption swelling can damage coal rock, which can be distinguished by fractal dimension. A fitting relationship between the adsorption damage and fractal dimension is proposed by experimental testing and theoretical analysis. High gas adsorption pressure proves to be the dominant factor that leads to coal failure softening and gas outburst disasters. Three main parameters concerning adsorption damage include the change rate of released energy density, the transition difference in the post-peak acoustic emission (AE) b value and the change rate of cumulative AE energy. Results show that all the three parameters present a step-type decreasing change with the increase in fractal dimension, and the fractal dimension shows a linear relationship within the same failure mode. Finally, a method is proposed to evaluate coal rock disaster transformation, based on the aforementioned three main parameters of adsorption damage.